EU’s Legal Framework on Personal Income Tax and Suggestions for Asean to Protect The Rights of Taxpayers - Kien Trung Doan (Advanced Studies on Socio-Economy Development, 2022)
The European Union (EU) has a complete and standard legal system, which is always the object of research and evaluation to learn for many countries. The EU comprises countries with an appropriate personal income tax system to ensure human rights. To ensure equality and human rights, and development in every member state, the EU seeks to harmonise personal income tax law, an area primarily of national jurisdiction. This article aims to study and evaluate some basic regulations that the EU has issued to create compatibility of the personal income tax law of the member states, better ensure human rights and promote the development of the Union. Based on the experiences of the EU, the article analyses some implications for the harmonisation of personal income tax law within the ASEAN from the perspective of international private law. Keywords: Personal Income Tax, Legal Harmonisation, EU, ASEAN